Longitudinal phase space manipulation with planar corrugated wakefield structures - Dong, Zhichao; Chen, Han; Song, Chuangye; Tan, Yuemei; Tian, Qili; Zhang, Hongze; Zhou, Zheng; Li, Zizheng; Du, Yingchao; Li, Renkai; Yan, Lixin; Huang, Wenhui; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
Wakefield structures have found a broad range of applications in beam longitudinal phase space manipulation in recent years. In this paper, we report on several electron beam manipulation experiments with planar corrugated wakefield structures following a photocathode RF gun, in which the bunch length of the electron beams are much longer, comparable, and much shorter than the characteristic wavelength of the corrugated structures, respectively. (1) A 15.6-ps beam forms a 0.17-THz bunch train via ballistic bunching, after gaining periodic energy modulation through these structures via self-induced wakefield. (2) For a 6-ps beam, the combination of wake structures and a drift converts its flat-top longitudinal profile into a ramped shape, remarkably improving its capability of efficiently exciting electromagnetic fields in plasma. (3) A 0.2-pC, 250-fs electron pulse subject to a drive beam’s wake is manipulated for different purposes, such as acceleration or deceleration with a ±200 keV gain in energy; or compression to ∼70 fs via ballistic compression. The results illustrate the unique and versatile capability of wakefield structures in beam manipulation for various applications. The simplicity, robustness, and inherent synchronization of such devices may open up many new possibilities in accelerator facilities.